JOB SATISFACTION EVALUATION OF EMPLOYEES IN CHINA: AGE DIFFERENCES. (16th November 2018) - Hong, L; Park, N; Sun, F
Abstract: Purpose: This study aimed to investigate what factors influence employees' job satisfaction and whether they differ across age groups. Methods: The secondary data came from the 2014 China Labor-force Dynamics Survey, which included 6, 249 employees in three age groups: 634 aged 55 and older, 2, 569 aged 40–54, 3, 046 aged 18–39. In this paper, job satisfaction was measured as the total subjective feeling that an employee feels about his/her work. After reviewing descriptive statistics, multiple regression models of job satisfaction were estimated by three age groups. Results: Among the three age-groups, the older employees had the highest evaluations of income, job safety, working environment, working time, job fun and total job satisfaction. The middle-aged employees had the highest evaluations of others' respect for their jobs. The younger group had the highest evaluations of promotion opportunity, job fun, relationship with coworkers, ability and skills use, others' respect, and opportunities to express opinions. Additionally, older group did not value job safety, relationship with coworkers, ability and skills use for their job satisfaction, however, younger and middle-aged employees did so. Discussion: The findings highlight the importance to examine employees' needs across life span. To promote job satisfaction, age-related challenges and psychological needs should be considered in work places.